A formação do farmacêutico e as diretrizes curriculares nacionais - Reis, Samuel Roosevelt Campos dos (Universidade Federal de São Carlos, 2016)
The objective of present study was analyze how much the pharmaceutical education got close or distant of the competences and capacities required for the National Curricular Guidelines (DCN) published in 2002 for the pharmacy courses. Participated this study four public university of São Paulo state. This study started from Documental Analyze of Political Pedagogical Projects (PPP), followed of Content Analyze (AC) of interview realized with pharmacy course directors. Through construction and application of a evaluative matrix was observed the curricular approximation and restructuration that way to keep generalist characteristic formation, this fact got highlight in some IES, for long 30 years or more dedicated at modalities formations pertinent the professional activities on drugs industry, clinical and toxicology’s tests, and foods. Furthermore, the curricular structure maintained separated among basic cycle and professional cycle, was justified for the stronger presence of traditional teaching- learning methodology and evaluation, reflected difficulties in the curricular integration, in addition to social integration not satisfactory, resulting some detachment of DCN. The renovation lack of pedagogics practices represented one fragility on curricular integration, like the humanist formation backed to Public Health System (SUS) approximation. However, the curricular restructuration showed be a constant discussion in enrolled IES, demonstrated some disquietude started from DCN e opened the way of the change and transformation way on pharmaceutical teaching.
Keywords: Farmácia; Diretrizes curriculares nacionais; Projeto político pedagógico; Sus (sistema único de saúde); Pharmacy; National curricular guidelines; Pedagogics politics projects; Public health system; CIENCIAS DA SAUDE